A Review on Literary Aspect of “Kanta Lauha” - Sanoop, K (International Research Journal of Ayurveda & Yoga, 2024)
Rasoushadhis(Mineral and metallic drugs) plays an important role in Ayurvedic therapeutics because of their unique qualities such as quick action, minimum dose and tastelessness. Rasayana(Rejuvenation) and Yogavahi (Catalytic activity) are characteristics of a properly made herbo-mineral preparation, which is also nontoxic, readily absorbable, adaptable and assimilable in the body. Bhasmas are unique Ayurvedic metallic/mineral preparation, treated with herbal juice or decoction to form organometallic complexes, and are widely recommended for treatment of a variety of chronic ailments. The incinerated iron preparations of Ayurveda are known as Lauha Bhasma(Incenerated iron). In Samhitha period Ayas(Iron) was used in the form of fine powder. Kanta Lauhais considered as best variety among Lauhas for Lauha Bhasma compared with Teekshna and MundaLauha.Kanta Lauha is chemically Fe3O4 (magnetite) as per API. Pure magnetite contains 72.4% of Iron, but since this metal never occurs alone, the metal content of real ores is lower. o, an attempt has been made in this article to gather all the possible information regarding KantaLauha explained in Rasashastra classical textbooks.